2020
DOI: 10.1146/annurev-micro-011320-015542
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Volatile Compounds: Functions in Communication, Cooperation, and Competition

Abstract: Bacteria produce a multitude of volatile compounds. While the biological functions of these deceptively simple molecules are unknown in many cases, for compounds that have been characterized, it is clear that they serve impressively diverse purposes. Here, we highlight recent studies that are uncovering the volatile repertoire of bacteria, and the functional relevance and impact of these molecules. We present work showing the ability of volatile compounds to modulate nutrient availability in the environment; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 101 publications
1
45
0
Order By: Relevance
“…The RL1 genome harbors genes related to the production of volatiles, exopolysaccharides and proteases, which are important in microbial communication, plant colonization and microbial detection by the host ( Flemming et al, 2016 ; Netzker et al, 2020 ). The chemotaxis protein CheY relevant for the transmission of sensory signals from the chemoreceptors to the flagella motors, which is additionally a microbe-associated molecular pattern (MAMP) ( Paul et al, 2010 ) was identified in the RL1 genome.…”
Section: Discussionmentioning
confidence: 99%
“…The RL1 genome harbors genes related to the production of volatiles, exopolysaccharides and proteases, which are important in microbial communication, plant colonization and microbial detection by the host ( Flemming et al, 2016 ; Netzker et al, 2020 ). The chemotaxis protein CheY relevant for the transmission of sensory signals from the chemoreceptors to the flagella motors, which is additionally a microbe-associated molecular pattern (MAMP) ( Paul et al, 2010 ) was identified in the RL1 genome.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that several beneficial microorganisms can promote iron uptake by plants based on the mechanisms of chelation, reduction, acidification and induction, among which the induction of plant systemic resistance mediated by volatile organic compounds (VOCs) has attracted wide attention in recent years (Back et al, 2020). Compared with soluble compounds, the VOCs released by rhizosphere microorganisms have two advantages in the interaction of microbial communities: first, volatile compounds with low molecular weights (<300 Da) can evaporate and migrate freely via soil pores over long distances (Sharifi and Ryu, 2018a,b); second, these gaseous substances act as signal molecules and can activate or enhance plant defense responses (Fincheira and Quiroz, 2018;Netzker et al, 2020). Some studies showed that Bacillus subtilis GB03 directly and indirectly promoted the growth of Arabidopsis thaliana under iron deficiency through the emission of acetoin and 2,3-butanediol (Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many microbial species such as Bacillus spp., Pseudomonas spp., Trichoderma spp., Streptomyces spp., and Acinetobacter spp. have been shown to effectively control FOC ( Raza et al, 2017 ; Kumar et al, 2020 ; Netzker et al, 2020 ). The primary mechanism probably involves secreting antimicrobial compounds, competing for biological niche and nutrients, and inducing plant resistance ( Shafi et al, 2017 ; Netzker et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%